MEDIA WORDWALL SEBAGAI SOLUSI KEAKTIFAN SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA - Khoirunnisa; Emy Yunita Rahma Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Interactive and innovative learning is essential to enhance students’ learning engagement in Pancasila education. One supporting media is the Wordwall application. This study aims to describe the implementation of Wordwall in Pancasila education on the topic “Practicing Pancasila Values” and to analyze the supporting and inhibiting factors affecting students’ learning engagement in grade IV at SDN Talun Kidul. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results indicate that the implementation of Wordwall involves three stages: planning, execution, and evaluation. The application creates an enjoyable, interactive learning environment that encourages students to be more active and facilitates understanding of the material. Supporting factors include high learning interest, adequate facilities, teacher creativity, and experience-oriented learning, while inhibiting factors consist of unstable internet access, differences in students’ understanding, and limited learning time. Overall, the use of Wordwall proves effective in enhancing students’ engagement with Pancasila values, making the learning process more meaningful and attractive